2020
DOI: 10.3390/cancers12051316
|View full text |Cite
|
Sign up to set email alerts
|

Relapse-Free Survival and PD-L1 Expression in First High- and Low-Grade Relapsed Luminal, Basal and Double-Negative P53-Mutant Non-Muscular Invasive Bladder Cancer Depending on Previous Chemo- and Immunotherapy

Abstract: The goal of this study was to assess how PD-L1 expression in tissue specimens of patients with main molecular subtypes of NMIBC (luminal, basal and double-negative p53-mutant) associates with relapsed-free survival in dependence on the tumor grade and prior treatment of primary bladder cancer. PD-L1 expressions on the membrane of neoplastic and CD8+ immune cells were assessed in tumor specimens (n = 240) of primary and relapsed luminal, basal and double-negative p53-mutant NMIBC. Association between relapse-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Based on the recent studies, we narrowed our current research focus on three molecular pathways—immune checkpoint axis PD1/PD-L1, fibroblast growth factor receptor 3 expression status, and tumor-dependent miRs. The prognostic role of PD-L1 for bladder cancer progression and the treatment success of immune checkpoint inhibitors have been rigorously evaluated in many studies [ 7 , 8 , 9 , 10 , 11 , 12 ]. In our previous study, we demonstrated that PD-L1 expression level correlated with RFS in relapsed aggressive non-muscular invasive bladder carcinoma of the luminal molecular subtype (GATA3-expressing NMIBC) [ 12 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the recent studies, we narrowed our current research focus on three molecular pathways—immune checkpoint axis PD1/PD-L1, fibroblast growth factor receptor 3 expression status, and tumor-dependent miRs. The prognostic role of PD-L1 for bladder cancer progression and the treatment success of immune checkpoint inhibitors have been rigorously evaluated in many studies [ 7 , 8 , 9 , 10 , 11 , 12 ]. In our previous study, we demonstrated that PD-L1 expression level correlated with RFS in relapsed aggressive non-muscular invasive bladder carcinoma of the luminal molecular subtype (GATA3-expressing NMIBC) [ 12 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic role of PD-L1 for bladder cancer progression and the treatment success of immune checkpoint inhibitors have been rigorously evaluated in many studies [ 7 , 8 , 9 , 10 , 11 , 12 ]. In our previous study, we demonstrated that PD-L1 expression level correlated with RFS in relapsed aggressive non-muscular invasive bladder carcinoma of the luminal molecular subtype (GATA3-expressing NMIBC) [ 12 , 25 ]. Kang et al showed that the FGFR3 expression level and its gene mutation status associated it with survival in primary pT1 bladder cancer [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations